Equus caballus з Ольвійського поховання - Маркова, О.В. (Археологія, 2002)
У статті наведено виміри та подано характеристику поки що єдиного, що потрапив до археозоологів, майже повного (за винятком правої передньої кінцівки) скелета коня з ольвійського некрополя. Для определения типов и пород лошадей бесценным материалом являются целые скелеты. Подобная находка на ольвийском некрополе — первая, попавшая к археозоологам, но не единственная; скелет, выкопанный в 1979 г., к сожалению, не был обработан. Вполне вероятно, что захоронения лошадей — это жертвоприношения Посейдону.
В статье приводятся промеры и характеристики скелета кобылы 2,5—3 лет, захороненной над входом в склеп римского времени неграбленого двойного погребения мужчины и женщины. Интересны два показателя — ширина лба и высота нижней челюсти, свойственные лошадям западного типа, при всех остальных, близких к лошадям восточного типа. Подобное сочетание, возможно, есть следствие скрещивания лошадей, которых либо разводили сами ольвиополиты, либо покупали у соседних племен, с лошадьми, завезенными из Западной Европы, что может быть еще одним свидетельством тесных торгово-экономических отношений Ольвии с другими регионами. Entire skeletons of horses are extremely valuable material for identifying their types and breeds. Such a find in the Olbian necropolis is the first one, which has fallen into archaeozoologists’ hands, though it is not the solitary one. The skeleton, found in 1979, was not studied properly. The horse burials must have been the sacrifice to Poseidon. The measurements and characteristics of the skeleton of a 2.5 — 3-year-old mare are given in the paper. The mare was buried over the entrance into the vault, with the not-robed double burial (of a man and a woman) of the Roman period. Two indices are of the most interest: the width of the forehead and the height of the lower mandible, peculiar to the horses of the western type, while the rest indices are closer to the horses of the eastern type. Such a combination was caused by the interbreeding of horses, which had either been reared by the Olbiopolites themselves or had been purchased by the neighboring tribes with the horses brought from Western Europe. This fact is another evidence of the close trade-economic relations of Olbia with the other regions.